Effect of heat stress alleviation on plasma protein, metabolites and lipid profile in lactating Nili-Ravi buffaloes under tropical climate - DAS, K S; SINGH, J K; SINGH, G; NAYAN, V (The Indian Journal of Animal Sciences, 2013)
Nili-Ravi lactating buffaloes (42) of Central Institute for Research on Buffaloes, Regional Station-Bir Dosanjh, Nabha, Patiala, Punjab were used to find out the effect of heat stress management on plasma protein, its metabolites and lipid profile during hot-dry (HD) and hot-humid (HH) seasons. All buffaloes were uniformly divided into 2 groups of 21 in each group. Out of which 10 buffaloes from each group were selected for blood sampling considering their lactation number, stage of lactation, body weight, dam’s milk yield and milk yield in current lactation. The control (T0) group buffaloes were kept in separate shed without any extra nutrient supplementation and modification in microclimate and management. The treatment (T1) group was supplemented with niacin, yeast, edible oil and provided curtains and mist fans in the shed, and altered feeding time, frequency and type of ration. Four samplings from each season were done for plasma albumin, globulin, albumin globulin ratio, total protein, blood urea nitrogen (BUN), urea, uric acid, creatinine, cholesterol, HDL cholesterol and triglyceride. Total protein was noted to be slightly higher in control than treatment group during HD season. Almost similar values were recorded in both groups (8.13 g/dL vs. 8.14 g/dL) during HH seasons. The values did not significantly differ between the groups. The buffaloes under HD season had significantly higher plasma cholesterol and HDL cholesterol in T1 (80.07 mg/dL and 31.63 mg/dL) than T0 (62.83 mg/ dL and 24.20 mg/dL) group. The HH season also showed similar result. The values of plasma albumin, globulin, albumin globulin ratio, BUN, triglyceride, urea, uric acid and creatinine were also found to be almost similar values in both groups during HD and HH seasons. It can be concluded that plasma total protein, BUN, metabolites and triglyceride are either very little affected or unaffected by the heat stress in buffaloes. The change in plasma cholesterol and HDL cholesterol might be due to either combine effect of management factors or only effect of nutrient supplementation that needs further investigation.